Prion-related peripheral neuropathy in sporadic Creutzfeldt-Jakob disease - Baiardi, Simone; Redaelli, Veronica; Ripellino, Paolo; Rossi, Marcello; Franceschini, Alessia; Moggio, Maurizio; Sola, Patrizia; Ladogana, Anna; Fociani, Paolo; Magherini, Anna; Capellari, Sabina; Giese, Armin; et al. (Journal of neurology, neurosurgery and psychiatry, 2019)
ObjectiveTo assess whether the involvement of the peripheral nervous system (PNS) belongs to the phenotypic spectrum of sporadic Creutzfeldt-Jakob disease (sCJD).MethodsWe examined medical records of 117 sCJDVV2 (ataxic type), 65 sCJDMV2K (kuru-plaque type) and 121 sCJDMM(V)1 (myoclonic type) subjects for clinical symptoms, objective signs and neurophysiological data. We reviewed two diagnostic nerve biopsies and looked for abnormal prion protein (PrPSc) by western blotting and real-time quaking-induced conversion (RT-QuIC) in postmortem PNS samples from 14 subjects.ResultsSeventy-five (41.2%) VV2-MV2K patients, but only 11 (9.1%) MM(V)1, had symptoms or signs suggestive of PNS involvement occurring at onset in 18 cases (17 VV2-MV2K, 9.3%; and 1 MM(V)1, 0.8%) and isolated in 6. Nerve biopsy showed a mixed predominantly axonal and demyelinating neuropathy in two sCJDMV2K. Electromyography showed signs of neuropathy in half of the examined VV2-MV2K patients. Prion RT-QuIC was positive in all CJD PNS samples, whereas western blotting detected PrPSc in the sciatic nerve in one VV2 and one MV2K.ConclusionsPeripheral neuropathy, likely related to PrPSc deposition, belongs to the phenotypic spectrum of sCJDMV2K and VV2 and may mark the clinical onset. The significantly lower prevalence of PNS involvement in typical sCJDMM(V)1 suggests that the PNS tropism of sCJD prions is strain dependent.